2020
DOI: 10.3390/app10196959
|View full text |Cite
|
Sign up to set email alerts
|

Towards Semi-Automatic Generation of a Steady State Digital Twin of a Brownfield Process Plant

Abstract: Researchers have proposed various models for assessing design alternatives for process plant retrofits. Due to the considerable engineering effort involved, no such models exist for the great majority of brownfield process plants, which have been in operation for years or decades. This article proposes a semi-automatic methodology for generating a digital twin of a brownfield plant. The methodology consists of: (1) extracting information from piping and instrumentation diagrams, (2) converting the information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 60 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…To have a comprehensive digital twin generator, it is also necessary to implement and connect generation phases such as simulation software interface implementation, initial condition consideration, and equipment parameterization. To make this procedure more automatic, Sierla et al [9] introduced several rules to convert an intermediate graph model into a format suitable for steady state simulation software. Azangoo et al [42] demonstrated how machine learning can extract process parameters for digital twins from recorded process history.…”
Section: Automatic Generation Of Digital Twinsmentioning
confidence: 99%
See 1 more Smart Citation
“…To have a comprehensive digital twin generator, it is also necessary to implement and connect generation phases such as simulation software interface implementation, initial condition consideration, and equipment parameterization. To make this procedure more automatic, Sierla et al [9] introduced several rules to convert an intermediate graph model into a format suitable for steady state simulation software. Azangoo et al [42] demonstrated how machine learning can extract process parameters for digital twins from recorded process history.…”
Section: Automatic Generation Of Digital Twinsmentioning
confidence: 99%
“…Brownfield process systems are functioning plants that may have been developed and built before modern digital systems and may thus lack design information in an Industry 4.0 format. A preliminary study on the semiautomatic generation of a digital twin for a laboratory scale water process plant [9] was recently published. However, it was limited to a laboratory scale process plant with limited types of process equipment.…”
mentioning
confidence: 99%
“…The authors of [7] attribute the skepticism of many colleagues from the process industry about the assertiveness of a ''digital twin'' to the fact that ''it is often unclear to operators and contractors what added value can be generated from the digital twin and how business models can be designed in the digital world'' and point out that this has already been presented and published, e.g., in [8][9][10]. Nevertheless, many col-leagues from the process industry may indeed find it difficult in individual cases to deduce the economic benefit of a digitalization initiative, in particular as the majority of the publications are not the work of the process and operations engineers themselves, but of (service or academic) colleagues from the automation field, and in fact also describe what is possibleespecially in the area of predictive maintenance -rather than what is needed.…”
Section: Motivationmentioning
confidence: 99%
“…There are several applications for them in the process systems like monitoring, control system design, optimization and fault detection. Several attempts have been made by researchers to extract the physics-based Digital Twin from available sources of data in brownfield process systems like Piping and Instrumentation Diagrams (P&IDs) and 3D-scanned or computer-aided design (CAD) models of the systems [4]- [6].…”
Section: Related Workmentioning
confidence: 99%